2009
DOI: 10.1542/peds.2008-2217
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Staphylococcus aureus Colonization in Atopic Dermatitis Decreases Disease Severity

Abstract: Chronic use of dilute bleach baths with intermittent intranasal application of mupirocin ointment decreased the clinical severity of atopic dermatitis in patients with clinical signs of secondary bacterial infections. Patients with atopic dermatitis do not seem to have increased susceptibility to infection or colonization with resistant strains of S aureus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
326
1
22

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 455 publications
(363 citation statements)
references
References 35 publications
14
326
1
22
Order By: Relevance
“…Those in the treatment group had significant improvement in their AD severity scores versus those in the placebo group. 56 Areas of the body that were not submerged in the bleach-containing water, specifically the head and the neck, revealed no difference in AD severity scores between the 2 groups. The treatment was well tolerated, without any adverse effect, and without any increase in resistant strains of S aureus.…”
Section: Managing Infectious Triggersmentioning
confidence: 89%
See 2 more Smart Citations
“…Those in the treatment group had significant improvement in their AD severity scores versus those in the placebo group. 56 Areas of the body that were not submerged in the bleach-containing water, specifically the head and the neck, revealed no difference in AD severity scores between the 2 groups. The treatment was well tolerated, without any adverse effect, and without any increase in resistant strains of S aureus.…”
Section: Managing Infectious Triggersmentioning
confidence: 89%
“…56 Pruritus may occur even in patients who are colonized but not actively infected. Many patients with AD have sudden exacerbations of their disease that can be attributed to active infection with bacteria, most commonly S aureus, and active treatment of the infection subsequently improves the skin.…”
Section: Managing Infectious Triggersmentioning
confidence: 99%
See 1 more Smart Citation
“…3,[9][10][11] It has also been noted that the elimination of the bacteria can relieve the symptoms in AD patients. 4,5 However, the pathological mechanism underlying S. aureus-exacerbated AD remains to be addressed, and no publications have elucidated the cellular and molecular pathways by which epicutaneous S. aureus infection leads to the deterioration of AD. Therefore, the current study focused on the in vivo and in vitro effects of the S. aureus-associated NOD2/TLR2 ligands and revealed that NOD2 and TLR2 exacerbated AD-like skin inflammation and induced the activation of basophils and eosinophils by interacting with dermal fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…3 Therapeutic interventions to eliminate S. aureus have been shown to alleviate AD symptoms, suggesting a deteriorating role for S. aureus in the disease. 4,5 Percutaneous application of peptidoglycan (PGN), which is a cell wall component of S. aureus, induces eosinophil infiltration in the skin. 6 Lipoteichoic acid (LTA), another cell wall component of S. aureus, is widely present in AD skin lesions, and its amount detected in the skin correlate with the severity of AD.…”
Section: Introductionmentioning
confidence: 99%